1998
DOI: 10.1364/oe.2.000462
|View full text |Cite
|
Sign up to set email alerts
|

Surface emitted second-harmonic generation from a quasi-phase matched waveguide in an Al_xGa_1-xAs/Al_2O_3 microcavity

Abstract: . (1998). Surface emitted second-harmonic generation from a quasi-phase matched waveguide in an AlxGa1-xAs/Al2O3 microcavity. Optics Express, 2(12), 462-470. DOI: 10.1364/OE.2.000462 General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Yoo et al [33] again achieved a much-improved efficiency of 15% W −1 at 1.54 µm in AlGaAs waveguides due to a tighter optical confinement realized by a buried heterowaveguide. Janz et al [34] reported surface-emitted SHG near 1.55 µm from a QPM waveguide in Al x Ga 1−x As/Al 2 O 3 microcavity with an efficiency of 5 × 10 −3 % W −1 . Bouchard et al [41] measured an effective nonlinear susceptibility modulation of 0.02 pm V −1 in the 1.5-1.6 µm spectral range in Al x Ga 1−x As asymmetric quantumwell waveguides using SHG experiments, where the QPM was realized using ion-implantation-induced intermixing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yoo et al [33] again achieved a much-improved efficiency of 15% W −1 at 1.54 µm in AlGaAs waveguides due to a tighter optical confinement realized by a buried heterowaveguide. Janz et al [34] reported surface-emitted SHG near 1.55 µm from a QPM waveguide in Al x Ga 1−x As/Al 2 O 3 microcavity with an efficiency of 5 × 10 −3 % W −1 . Bouchard et al [41] measured an effective nonlinear susceptibility modulation of 0.02 pm V −1 in the 1.5-1.6 µm spectral range in Al x Ga 1−x As asymmetric quantumwell waveguides using SHG experiments, where the QPM was realized using ion-implantation-induced intermixing.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that, for a fixed sample length, the conversion efficiency is 1/m 2 times lower in mth-order QPM compared to first-order QPM. Earlier reports [31][32][33][34][35] on quasi-phase matched interactions in semiconductors involved the epitaxial growth of Al x Ga 1−x As on a patterned substrate, where the periodic crystal domain inversion was achieved using selective etching and wafer bonding. Although this method is direct, efforts were limited by relatively large losses in these structures.…”
Section: Quasi-phase-matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…22 (a)). Building on previous work in parametric oscillation and Raman [61,61,62,64,187,342], silica microtoroids were used for generating and studying broadband Kerr frequency combs in 2007. [317] Benefiting from the smooth surface of the devices, quality factors of the silica toroids can achieve over 10 8 easily, which greatly enhances the circulating power inside the cavity and boosts comb generation.…”
Section: Silicon Dioxidementioning
confidence: 99%